Risk factors for mortality within one-year after implantable cardioverter defibrillator implantation: a nationwide study. (25th November 2020) - Alhakak, A; Ostergaard, L; Butt, J.H; Vinther, M; Philbert, B.T; Jacobsen, P.K; Yafasova, A; Torp-Pedersen, C; Kober, L; Fosbol, E; Mogensen, U.M; Weeke, P.E
Abstract: Background: Current guidelines do not recommend implantable cardioverter defibrillator (ICD) implantation in patients with an estimated survival probability of less than one year. There is still an unmet need to identify patients who are unlikely to benefit from an ICD. Purpose: We determined one-year mortality after ICD implantation and associated risk factors of one-year mortality. Methods: Using Danish nationwide registries from 2000–2016, we identified patients ≥18 years old undergoing first-time ICD implantation for primary or secondary prevention. Patients were followed for up to one-year from time of ICD implantation. Risk factors associated with one-year mortality after time of ICD implantation were evaluated in multivariable logistic regression models. Results: A total of 13, 344 patients underwent first-time ICD implantation (median age: 66 years [25th-75th percentile 58–72 years], male=81.3%, secondary prevention=54.6%), of which 647 died (4.8%) within one year of follow-up. Compared with ICD patients who survived for one year, those who died were significantly older (72 years vs. 66 years, p<0.001) and had more comorbidities, including congestive heart failure (70.8% vs. 63.4%), atrial fibrillation (36.6% vs. 23.6%), diabetes (30.8% vs. 19.9%), chronic obstructive pulmonary disease (COPD) (17.0% vs. 8.2%), chronic renal disease (13.0% vs. 4.4%), malignancy (9.9% vs. 5.4%), and dialysis (7.3% vs. 2.4%) (p<0.001 for all). Results from the multivariable logistic regression model are depicted in the Figure. There was a graded relationship between age and one-year mortality, with a greater risk of all-cause mortality with increasing age. In addition, dialysis, chronic renal disease, COPD, malignancy, diabetes, and congestive heart failure were strongly associated with increased risk of one-year all-cause mortality. However, ischaemic heart disease was associated with a lower risk of all-cause mortality (Figure). The one-year risk of death was 13.2% for both patients receiving dialysis and patients with chronic renal disease, respectively. The majority of deaths within one year were attributed to cardiovascular causes (408/647, 63.1%) of which chronic ischaemic heart disease (68/647, 10.5%), acute myocardial infarction (50/647, 7.7%), and atherosclerosis (40/647, 6.2%) were the most common. The most common non-cardiovascular cause of death was malignancy (10.5%). Conclusion: In patients with a first-time ICD implantation, 95% survived for more than one year after implantation. While low mortality rates are indicative of relevant patient selection for ICD implantation, advanced age, dialysis, and several comorbidities were all strongly associated with increased one-year mortality, whereas ischaemic heart disease was associated with a lower risk of one-year mortality. Potential benefit of an ICD in such patients should be carefully evaluated before implantation. Funding Acknowledgement: Type of funding source: None